Marginal parental donors for pediatric living donor liver transplantation. Issue 4 (August 2022) - Kasahara, Mureo; Sakamoto, Seisuke; Fukuda, Akinari; Uchida, Hajime; Yi, Nam-Joon; Schlegel, Andrea; Muiesan, Paolo; Qiang, Xia; Gao, Wei; Zhu, Zhi-Jun; Rodriguez-Davalos, Manuel; Rela, Mohamed
Abstract : Purpose of review: Living donor liver transplantation (LT) has been increasingly recognized as an effective treatment modality with excellent patient survival. Indications for LT have evolved not only for cholestatic liver disease, but also metabolic liver diseases. Living donor selection, particularly for pediatric inherited disease, is essential to prevent morbidity, both in the donor and recipient. Recent findings: Based on 30 years of experience in pediatric living donor LT in Japan, we could identify marginal parental living donors who have potential risks following LT, including heterozygous mothers with ornithine transcarbamylase deficiency, heterozygous protein C deficiency, heterozygous hypercholesterolemia, heterozygous protoporphyria, asymptomatic parental donors with paucity of intrahepatic bile duct, and human leukocyte antigen-homozygous parental donors. Summary: Although these situations seem rare due to infrequency of the condition, careful living donor evaluation is required to optimize the outcomes for pediatric recipients. In the setting of an appropriate selection of a living donor, we should avoid any additional hazards, given that the procedure itself has risks for a healthy individual.